Upaya Perkembangan Kemampuan Motorik Kasar Melalui Permainan Tradisional Engklek di Kelompok Bermain Daarul Aulad Ciparay - Munadhilah, Faiha Jabiratullfatihah; Hadianti, Asti Nur (Pijar Pelita: Journal of Early Childhood Education and Early Childhood Islamic Education, 2025)
Traditional games are part of a cultural heritage with numerous educational values and great potential to support children's growth process in their early age. However, traditional games are starting to be replaced by modern games that focus less on children's physical development. One of the skills that is very important to develop early is gross motor skills. This study aims to improve the gross motor skills of early childhood by applying traditional games called Engklek at KB Daarul Aulad Ciparay. The method applied was Classroom Action Research (CAR), which was conducted in two cycles involving 20 children aged 5 to 6 years. Data was collected through observation with assessment tools that assess aspects of balance, agility, and speed. The results of the study showed an increase in the average gross motor skills of children from 91.66% in cycle I to 94.99% in cycle II. The findings suggest that Engklek is effective as a learning tool to develop children's gross motor skills in a fun and contextualized way.